Legal imaginaries of crisis and fear : dark constitutionalism - Belov, Martin (Nomos studies in law, culture, and power., 2026)
"This book explores the epistemological, semiotic, semantic, and heuristic dimensions of the dark emotions in constitutional and international law. We are living in times of crisis and emergency where negative emotions and dark feelings are abundant. As these have come to form the intellectual and socio-legal context for the performance of constitutional and international law, this book explores their place - especially the politics of fear, but also anger, hate, despair, and crisis - in our current constitutional polycrisis. Focusing on this 'dark constitutionalism', the book draws together an international and interdisciplinary range of scholars to consider the place of emotive semiotics in collective meaning making, the constitutional politics of emotions, and emotional approaches to global challenges in a time of crisis, emergency, and transition. The book thereby develops a compelling analysis of the use of negative emotions in the shaping of contemporary constitutional imaginaries, and with it a novel account of the rise of dark constitutionalism. This book will appeal to researchers and scholars working in the areas of legal theory, legal philosophy, constitutional law, international law and socio-legal studies"-- Provided by publisher.